The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1055/s-2005-921049
|View full text |Cite
|
Sign up to set email alerts
|

Virtual Reality Colonoscopy Simulation: A Compulsory Practice for the Future Colonoscopist?

Abstract: Skills acquired using the AccuTouch simulator transfer well into the clinical colonoscopy environment. The results of this trial clearly support the plan to integrate simulator training into endoscopic education curricula.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
80
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(80 citation statements)
references
References 8 publications
0
80
0
Order By: Relevance
“…In medicine, haptic feedback has mostly been used for surgical training simulations [10]. Indeed, Ahlberg et al demonstrated that simulator training significantly improved the initial learning curve for the simulatortrained over the control group [11].…”
Section: Discussionmentioning
confidence: 99%
“…In medicine, haptic feedback has mostly been used for surgical training simulations [10]. Indeed, Ahlberg et al demonstrated that simulator training significantly improved the initial learning curve for the simulatortrained over the control group [11].…”
Section: Discussionmentioning
confidence: 99%
“…The total time trainees spent on VR simulator varied from 5 till 10 h [15][16][17][18]. One study showed that there is a need of a 20-h exposure for a novice trainee to reach the level of an expert in colonoscopy [18]. In our case, we are going to have a look at how many hours of exposure users need to do the whole procedure of PD independently without help and mistakes.…”
Section: Discussionmentioning
confidence: 99%
“…There are studies in which the exposure within formalized teaching settings was controlled. The total time trainees spent on VR simulator varied from 5 till 10 h [15][16][17][18]. One study showed that there is a need of a 20-h exposure for a novice trainee to reach the level of an expert in colonoscopy [18].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the average expert intubation time was with 438 seconds close to the 7 minutes on the same simulator case that trainees needed before starting clinical colonoscopies in the training study by Ahlberg et al [74]. Also, since all novices reached the endpoints, they were confirmed not too challenging.…”
Section: Discussionmentioning
confidence: 95%
“…In hindsight, the NP endpoint may have been too strict, making it too difficult to reach the learning curves endpoint. There are alternatives, such as requiring that more than 97% of the procedure time is free of patient discomfort, used by Ahlberg et al [74]. However, this was considered too easy for this task and would fail to enforce realistic loop detection and straightening techniques.…”
Section: Discussionmentioning
confidence: 99%